Primary Epididymal Adenocarcinoma: Case report and Review of the Literature - Kolesari?, Nives; Le?, Cvjetko; Kirigin, Monica Stephany; Balagovi?, Ivica; Krušlin, Bozo (Archives of Clinical and Biomedical Research, 2026)
Primary epididymal adenocarcinoma (PEA) is an extremely rare tumor, with fewer than 30 cases reported in the English literature. The diagnosis of PEA is based on histological examination and comprehensive clinical evaluation to exclude metastatic adenocarcinoma. We report a case of primary adenocarcinoma of the epididymis in a 63-year-old man presenting with hydrocele. The patient underwent right radical orchiectomy, and the diagnosis of PEA was established. This case demonstrates the importance of pathological examination and the consideration of a malignant differential diagnosis in an apparently benign pathology such as hydrocele, as well as the use of different diagnostic methods to rule out metastatic adenocarcinoma of the epididymis.